Subtilase from Beauveria sp.: conformational and functional investigation of unusual stability - Dalal, Sayli A.; More, Snehal V.; Shankar, Shiv; Laxman, Ryali Seeta; Gaikwad, Sushama M. (European Biophysics Journal With Biophysics Letters, 2014)
Retention of total activity of the subtilisin-like serine protease from Beauveria sp. MTCC 5184 (Bprot) in the vicinity of (1) 3 M GdnHCl for 12 h, (2) 50 % methanol and dimethyl sulfoxide each for 24 h, and (3) proteolytic enzymes (trypsin, chymotrypsin, and proteinase K) for 48 h led to expect the enzyme to be a kinetically stable protein. Also, the structure of the protein was stable at pH 2.0. Biophysical characterization and conformational transitions were monitored using steady-state and time-resolved fluorescence, FTIR, and CD spectroscopy. Single tryptophan in the protein exists as two conformers, in hydrophobic and polar environment. The secondary structure of Bprot was stable in 3 M GdnHCl as seen in far-UV CD spectra. The active fraction of Bprot obtained from size-exclusion chromatography in the presence of GdnHCl (1.0-3.0 M) eluted at reduced retention time. The peak area of inactive or denatured protein with the same retention time as that of native protein increased with increasing concentration of denaturant (1.0-4.0 M GdnHCl). However, the kinetics of GdnHCl-induced unfolding as studied from intrinsic fluorescence revealed k (unf) of native protein to be 5.407 x 10(-5) s(-1) and a half-life of 3.56 h. The enzyme is thermodynamically stable in spite of being resistant to the denaturant, which could be due to the effect of GdnHCl imparting rigidity to the active fraction and simultaneously unfolding the partially unfolded protein that exists in equilibrium with the folded active protein. Thermal and pH denaturation of Bprot exhibited interesting structural transitions.
Keywords: Beauveria; Chemical denaturation; Conformational transitions; Serine protease; Subtilase; Thermal denaturation; Thermodynamic stability

Eco-friendly enzymatic dehairing of skins and hides by C-brefeldianus protease - Khandelwal, Harish B.; More, Snehal V.; Kalal, K. M.; Laxman, Ryali Seeta (Clean Technologies and Environmental Policy, 2015)
Alkaline protease from Conidiobolus brefeldianus was efficient in unhairing various types of skins and hides. The crude protease preparation was active toward keratin-azure, elastin-orcin, azocasein, and azocoll, but did not show true collagenase activity. In addition, the crude enzyme exhibited other enzyme activities such as chondroitinase, laminarase, and chitinase. Complete hair removal of skin/hide by the protease achieved in 16-18 h. The dehaired pelt showed smooth and white appearance due to hair removal along with epidermal layer. In addition, the grain was clean and without damage in enzymatically dehaired pelts. The microscopic observation of the cross-section of dehaired goat skin and cow hide showed absence of epidermis, hair shaft with empty follicles. Enzymatic dehairing resulted in complete and uniform fiber opening in the dermis and corium region. Physical properties viz. tensile strength, elongation, and tear strength of dyed crust of enzymatically and conventionally dehaired pelts were comparable. Results were also validated on large scale with goat skins and cow hides.
Keywords: Alkaline Protease; Conidiobolus brefeldianus; Cow hides; Dehaired pelts; Enzymatic dehairing; Sheep skins

Silk degumming and utilization of silk sericin by hydrolysis using alkaline protease from beauveria Sp. (MTCC 5184): a green approach - More, Snehal V.; Chavan, Sakalya; Prabhune, Asmita Ashutosh (Journal of Natural Fibers, 2017)
Conventionally, degumming is carried out at 90°C--110°C temperature by boiling the raw silk with Marseilles soap and sodium bicarbonate which eventually requires a lot of water and energy. In this study, degumming of Chinese bivoltine raw silk fibres with alkaline protease produced by Beauveria sp. (MTCC 5184) is studied. Complete degumming was obtained in 45 min with 75 units of enzyme per gram of silk. Degumming was found to be optimal at 50°C and pH 9.0. Scanning electron micrographs showed that the sericin deposits were removed and the obtained fibres were clean, separated, had smooth feel with shine as compared to untreated fibres. Sericin isolated from silk cocoon (by-product which goes waste) was hydrolyzed with the same alkaline protease obtained from Beauveria sp. to get small molecular weight peptides. These peptides can be utilized further for cosmetic, pharmaceutical, and various industrial applications.
Keywords: Alkaline Protease; bivoltine; degumming; Silk; weight loss